2020
DOI: 10.1101/2020.09.21.20198911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental impact of Personal Protective Equipment supplied to health and social care services in England in the first six months of the COVID-19 pandemic

Abstract: Objectives Use of Personal Protective Equipment (PPE) has been central to controlling spread of SARS-CoV2. This study aims to quantify the environmental impact of this, and to model strategies for its reduction. Methods Life cycle assessment was used to determine environmental impacts of PPE supplied to health and social care in England during the first six months of the COVID-19 pandemic. The base scenario assumed all products were single-use, air freighted, and disposed via clinical waste. Scenario modellin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…However, in order to assess the whole environmental impact, it would be necessary to consider lifecycle analysis (LCA) of each type of face mask. Rizan et al (2021) used a LCA to determine environmental impacts of personal protective equipment (PPE) distributed to health and social care in England during the first six months of the COVID-19 pandemic. They concluded that the environmental impact could be reduced through different actions, among which it was the reuse of PPE.…”
Section: Resultsmentioning
confidence: 99%
“…However, in order to assess the whole environmental impact, it would be necessary to consider lifecycle analysis (LCA) of each type of face mask. Rizan et al (2021) used a LCA to determine environmental impacts of personal protective equipment (PPE) distributed to health and social care in England during the first six months of the COVID-19 pandemic. They concluded that the environmental impact could be reduced through different actions, among which it was the reuse of PPE.…”
Section: Resultsmentioning
confidence: 99%
“…The surge in mask usage to combat SARS-CoV-2 transmission has prompted research on the environmental impact of masks. Numerous elements can be considered, such as microplastics [10,12], carbon footprints of personal protective equipment (PPE) [42], and the prospect of biodegradable masks [11]. One study took a more comprehensive approach by examining four metrics: carbon footprint, non-renewable cumulative energy demand, water depletion according to the AWARE methodology (hereafter water footprint), and overall environmental impacts [43].…”
Section: Environmental Impactsmentioning
confidence: 99%
“…With cumulative use, even simple PPE has major consequences. A standard box of nitrile gloves, for example, has the same CO 2 equivalent as driving 20 miles in a petrol car 3. Simple and effective ways of minimising unnecessary PPE use include employing “runners” outside high risk areas to fetch equipment and drugs and the avoidance of “hygiene theatre” (conspicuous PPE use) in low risk settings.…”
mentioning
confidence: 99%
“…Zhang and colleagues focus on single use face masks1; reusable respirator masks and powered air purifying respirators are available, but they are seldom designed for healthcare and can be challenging to clean. Reusable gowns, laundered before re-circulation, have been widely adopted and reduce environmental effects by 65% 3. Recycling PPE presents challenges in terms of material separation and risk of contamination, so design should focus on single materials able to feed into closed loop recycling, complemented by regulatory approvals and systems facilitating safe handling.…”
mentioning
confidence: 99%